2021
DOI: 10.1111/imm.13391
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–T cell crosstalk in inflammatory bowel disease

Abstract: Neutrophils are the most abundant leucocytes in human blood, promptly recruited to the site of tissue injury, where they orchestrate inflammation and tissue repair. The multifaceted functions of neutrophils have been more appreciated during the recent decade, and these cells are now recognized as sophisticated and essential players in infection, cancer and chronic inflammatory diseases. Consequently, our understanding of the role of neutrophils in inflammatory bowel disease (IBD), their immune responses and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…Investigating associations between lesion LCH cells and other signaling factors, we found that the proportion of LCH cells in lesions correlated with plasma IL-11 (a cancer mediator), soluble CD27 (sCD27; a T cell activator) and plasma CCL2 (MCP-1; monocyte chemoattractant protein-1) ( Figure 1B.i–iii ). In addition to this study, it is already established that plasma IL-23 and IL-12p40, the two subunits of IL-23 - a well-established driver of chronic tissue inflammation ( 27 ), correlate with the proportion of LCH cells in the CD11c+ compartment of LCH lesions ( 19 ). The influence of plasma signaling factors on LCH cell phenotype and pathogenesis may be more complex than originally thought, and future studies addressing soluble and cellular immunological phenotypes during AD and NAD in LCH, both at the lesion site and in circulation, are warranted.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Investigating associations between lesion LCH cells and other signaling factors, we found that the proportion of LCH cells in lesions correlated with plasma IL-11 (a cancer mediator), soluble CD27 (sCD27; a T cell activator) and plasma CCL2 (MCP-1; monocyte chemoattractant protein-1) ( Figure 1B.i–iii ). In addition to this study, it is already established that plasma IL-23 and IL-12p40, the two subunits of IL-23 - a well-established driver of chronic tissue inflammation ( 27 ), correlate with the proportion of LCH cells in the CD11c+ compartment of LCH lesions ( 19 ). The influence of plasma signaling factors on LCH cell phenotype and pathogenesis may be more complex than originally thought, and future studies addressing soluble and cellular immunological phenotypes during AD and NAD in LCH, both at the lesion site and in circulation, are warranted.…”
Section: Resultsmentioning
confidence: 79%
“…In addition to this study, it is already established that plasma IL-23 and IL-12p40, the two subunits of IL-23 -a well-established driver of chronic tissue inflammation (27), correlate with the proportion of LCH cells in the CD11c+ compartment of LCH lesions (19). The influence of plasma signaling factors on LCH cell phenotype and pathogenesis may be more complex than originally thought, and future studies addressing soluble and cellular immunological phenotypes during AD and NAD in LCH, both at the lesion site and in circulation, are warranted.…”
Section: Resultsmentioning
confidence: 80%
“…In addition, FMT and biologics can jointly target the crosstalk between Th17 cells and neutrophils infiltrating the intestinal lamina propria to alleviate intestinal inflammation ( Pelletier et al, 2010 ). In the colonic lamina propria of patients with IBD, Th17 cells highly express IL-8 and mediate the recruitment of tissue-infiltrating neutrophils, which have been proven to be the main producers of IL-23 in the intestine in an IL-8/CXCR1/CXCR2-dependent manner ( Kvedaraite et al, 2016 ; Kvedaraite, 2021 ). These tissue-infiltrating neutrophils, in turn, present antigens and activate pathogenic Th17 cells with the aid of IL-23, thereby building a pro-inflammatory microenvironment and maintaining a sustained inflammatory response in the intestine ( Kvedaraite, 2021 ).…”
Section: Potential Application Of Gut Microbiota In the Biological Th...mentioning
confidence: 99%
“…In the colonic lamina propria of patients with IBD, Th17 cells highly express IL-8 and mediate the recruitment of tissue-infiltrating neutrophils, which have been proven to be the main producers of IL-23 in the intestine in an IL-8/CXCR1/CXCR2-dependent manner ( Kvedaraite et al, 2016 ; Kvedaraite, 2021 ). These tissue-infiltrating neutrophils, in turn, present antigens and activate pathogenic Th17 cells with the aid of IL-23, thereby building a pro-inflammatory microenvironment and maintaining a sustained inflammatory response in the intestine ( Kvedaraite, 2021 ). FMT decreased the number of neutrophils in the mucosal lamina propria, thereby reducing IL-23 production and antigen presentation to Th17 cells ( Burrello et al, 2018 ).…”
Section: Potential Application Of Gut Microbiota In the Biological Th...mentioning
confidence: 99%
“…However, with the persistence of the inflammatory process, neutrophils become necessary as parts of the resolution of inflammation, the initiation of wound healing, and the return of the system to homeostasis (Kolaczkowska and Kubes;Puhl and Steffens;Ma, 2021). Neutrophils have also been shown to modulate the effects of the adaptive immune system by manipulating cytokines necessary for both B-and T-cell survival and activation (Karmakar and Vermeren., 2021;Kvedaraite, 2021). Therefore, identifying the precise cellular mechanisms that regulate neutrophil trafficking and activation is of the utmost importance, especially when it comes to manipulating the immune response for a successful therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%